LUIS DE VALDIVIA AND THE SPATIAL ARTICULATION OF CHILE. - Díaz Blanco, José Manuel (Revista de Historia Social y de las Mentalidades, 2012)
This paper studies Father Luis de Valdivia Ìs (S.J.) perceptions and ideas about the Kingdom of Chile Ìs geographical articulation at the end of the 16th century and the beginnings of the 17th century. It asserts that these perceptions were based on the conception of Chile as a political and geographical unity, whilerecognizing its internal divisions (the “land of war”/“land of peace” dichotomy, the different character of the Spanish cities, the atomization of the indigenous societies of the Araucanía...) as well as an awareness of its subservient place within larger entities (the provincial order of the Society of Jesus, the Spanish Monarchy and the Christendom). The documental basis is a series of correspondence held in the Jesuit archives of Spain, Chile and Italy.